Validity of the People Risk Framework: Evidence from the FSA - Chrysostomou, Xenia (2013)
The recent Global Financial Crisis was the ultimate manifestation for the recognition and appreciation of people risk, one of the dimensions constituting operational risk, highlighting the necessity of people risk management within the financial industry. In recognition of the magnitude of its impact, ‘people risk’ became a ’hot’ topic amongst the financial regulators, which resulted in the stipulation of assigning capital reserves, exclusively dedicated to its coverage. However, the nature of people risk is attached with the impediment of broadness and diversity, which leaves operational risk managers victims of uncertainty of its unidentified boundaries. With the purpose of analysing people risk, and capturing its scope, McConnell (2008) has developed a theoretical framework consisting of four ‘escalating’ dimensions, namely; incident, individual, institution and industry. The aim of this paper is to examine the extent to which this theoretical framework is applicable in practice, by conducting a qualitative content analysis using the Financial Services Advisory Final Notices imposed on banks and insurance firms as evidence. The investigation attempts to find whether there is a correlation between the theoretical framework and the ‘real’ evidence, in order to evaluate its validity. The analysis finds that, in fact, there is evidence assuring its validity, yet there is room for improvements for more accurate outcomes. The study recommends that the framework should expand the dimensions constituting the framework. Possible suggestions are to include additional dimensions in relation to system and process risk, and the ‘Three lines of defence’ model.